1972
DOI: 10.1172/jci106792
|View full text |Cite
|
Sign up to set email alerts
|

Renin Activation in the Venous Plasma from the Involved Kidney in the Patient with Renal Hypertension

Abstract: A B S T R A C T Measurements of plasma renin activity (PRA) , however, were bilaterally equal in renal venous plasma from selected patients with renal hypertension who showed distinct differences in PRSA-20 min and PRA measurements. Prior extraction of plasma lipids did not significantly change the bilateral renal venous PRSA-20 min determinations. Stimulation of endogenous renin release in normal dogs did not change the PRSA determinations. The data suggest strongly the presence of a "renin activating" mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
1

Year Published

1974
1974
1991
1991

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 14 publications
0
5
1
Order By: Relevance
“…In apparent contrast to our results, Sambhi and Wiedeman [8] have reported that the re activity of renin during a 20-min incubation is increased in venous plasma of the more in volved kidney compared to that from the contralateral kidney in patients with pre dominately unilateral renal hypertension. The difference between our results and those of Sambhi and Wiedeman may in part be related to patient selection.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In apparent contrast to our results, Sambhi and Wiedeman [8] have reported that the re activity of renin during a 20-min incubation is increased in venous plasma of the more in volved kidney compared to that from the contralateral kidney in patients with pre dominately unilateral renal hypertension. The difference between our results and those of Sambhi and Wiedeman may in part be related to patient selection.…”
Section: Discussioncontrasting
confidence: 99%
“…Correlations between the demonstration of greater renin activity from the ischemic kidney compared to the normal, contralateral kidney and cure or improvement of hypertension following revascularization are high [6,7]. Sambhi and Wiedeman [8] have recently reported that the in vitro rate of angiotensin generation is also greater in venous effluent from the more involved kidney than from the contralateral kidney in patients with renal hypertension. The purpose of the present report is to describe our measurements of renal venous PRR in both experimental and clinical renovascular hypertension.…”
mentioning
confidence: 99%
“…Although the normal form of substrate is the major renin substrate form in all plasmas, the new forms of substrate may have a significant effect on the overall renin reaction in plasma because form III (Rf = 0.16) appears to lead to an accelerated rate of angiotensin production and form II (Rf = 0.35) decreases this rate. These new substrate forms may, therefore, possibly account for the altered kinetics of the renin reaction observed in some hypertensive states (13,14).…”
Section: Discussionmentioning
confidence: 99%
“…These components include renin substrate concentration and "renin reactivity," a measure of inhibitors or accelerators of the renin reaction. Accelerating factors (or the lack of inhibitors) producing an increase in renin reactivity have been observed in a variety of primary and secondary hypertensive states (12)(13)(14)(15)(16) and thus far appear to be common to all forms of hypertension studied. Our second objective was to examine these components of the renin reaction in coarctation hypertension, to assess their contribution to the conventional plasma renin activity, and to seek further insight into the pathophysiological significance of the in vitro renin reactivity measurement in hypertensive states.…”
mentioning
confidence: 99%
“…Increases have, however, been reported in a variety of other hypertensive states in man, including essential hypertension of both normal-and low-plasma renin activity categories (13,14), renovascular hypertension (12,15), and primary aldosteronism (16). The addition of coarctation hypertension to this group provides further evidence that increased renin reactivity is a common feature of most, if not all, hypertensive states.…”
mentioning
confidence: 99%